THE DEVELOPMENT AND EVALUATION OF A TELEVISED SCIENCE INSERVICE PROGRAM. - Piper, Martha K.; Butts, David P. (Journal of Research in Science Teaching, 1976)
The article investigates the development and evaluation of a televised science in-service program. About 76 elementary teachers were employed as participants for this study in the implementation of science inside the classroom while fifty teachers participated in the televised in-service program through cable television in their own schools. In this study, past experience has been defined as prior science hours taken, number of years taught and grade level taught. Accordingly, school districts are having difficulty in providing adequate staff development in assistance for teachers in implementing new curricula. It is said that accessibility to television is one efficient method for the utilization of time, place and resources in education.